New taxonomic data on the sac spiders (Arachnida: Araneae: Clubionidae) from China, with description of a new species - Yu, Hao; Sun, Zixuan; Zhang, Guren (Zootaxa, 2012)
The present paper deals with three Clubioninae species. The genus Pristidia Deeleman-Reinhold, 2001 is recorded for the firsttime from China, and a new species, P. ramosa sp. nov., is described from Mt. Jinggang of Jiangxi province, China. Theconspecific male of Clubiona linzhiensis Hu, 2001 is described for the first time. Clubiona dactyla Zhang & Zhu, 2009 is proposed as a junior synonym of C. altissimoides Liu et al., 2007.